2015
DOI: 10.1016/j.pnpbp.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the mGluR2/3 agonists as a therapeutic target for schizophrenia: Still promising or a dead end?

Abstract: Group II metabotropic glutamate receptor (mGluR2/3) agonists once showed promise as non-dopaminergic antipsychotic drugs because of their efficacy in alleviating symptoms of schizophrenia (SZ) in both animal models and human patients. However, the recent failure of Phase III clinical trials dealt a huge blow to the scientific community and the aftershock of the setback in mGluR2/3 research can be felt everywhere from grant support and laboratory studies to paper publication. An immediate question raised is whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 110 publications
(151 reference statements)
1
54
0
Order By: Relevance
“…1,2 Although initial trials with mGluR2/3 agonists have had mixed results, [3][4][5][6][7] data increasingly indicate that changes in mGluR3 are associated with schizophrenia and aging, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] encouraging this treatment strategy. Clinical trials were originally based on data from rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although initial trials with mGluR2/3 agonists have had mixed results, [3][4][5][6][7] data increasingly indicate that changes in mGluR3 are associated with schizophrenia and aging, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] encouraging this treatment strategy. Clinical trials were originally based on data from rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, increasing the activity of mGluR2/3 receptors might therefore be a viable treatment strategy. The upregulation of mGluR2/3 signaling using agonists or modulators of mGluR2/3 has been shown to have therapeutic potential in schizophrenia relevant behavioral paradigms (Li et al, 2015). However, none of these studies have assessed the potential of these agents to correct core NMDA-R and GABAA-R deficits and/or imbalances.…”
Section: The Mglur2/3 Agonist Ly379268 Restores Nmda-r and Gabaa-r Exmentioning
confidence: 99%
“…While the mGluR2/3 agonist LY2140023 has been discontinued during the clinical trial phase III due to a lack of significant improvement above placebo, more selective agonists, including LY379268, have been hypothesized to exert a stronger therapeutic action (Li et al, 2015).…”
mentioning
confidence: 99%
“…Similar problems occurred in the development of mGluR2/3 agonists, which act by inhibiting glutamate release (Li et al 2015). Despite a promising proof of concept study finding improved positive and negative symptoms after treatment with LY2140023 compared with placebo (Patil et al 2007), later trials were unsuccessful.…”
mentioning
confidence: 99%
“…Despite a promising proof of concept study finding improved positive and negative symptoms after treatment with LY2140023 compared with placebo (Patil et al 2007), later trials were unsuccessful. One follow-up multi-centre phase II trial was inconclusive, with a high placebo response rate (Kinon et al 2011), and another phase II open-label study found LY2140023 was inferior to a comparison atypical antipsychotic (Li et al 2015). In August 2012, Eli Lilly announced their decision to stop phase III trials as one of the trials, closest to completion, failed to meet its primary endpoint (Li et al 2015).…”
mentioning
confidence: 99%